An evaluation of iron ore tailings characteristics and iron ore tailings concrete properties. (7th June 2021) - Zhao, Jiangshan; Ni, Kun; Su, Youpo; Shi, Yunxing
Highlights: The material characteristics of IOT are summarized. The properties of IOT concrete are analyzed and compared with those of NS concrete. IOT concrete has satisfactory workability, mechanical properties and durability. The relationships between the mechanical properties of IOT concrete are established. The application of IOT into concrete achieves sustainable development. Abstract: Incorporating waste by-products in concrete is one of the critical approaches for sustainable development. Particularly, iron ore tailings (IOT) as ordinary industrial solid waste in China is discharged and deposited. This review is a recapitulation of the material characteristics of IOT and its effects on the workability, mechanical properties, and durability of concrete. The increasing development of ore beneficiation technology, along with the collection from various sources, results in the diversity of IOT characteristics. Owing to low pozzolanic activity, IOT is generally limited to substitute cement in concrete, so which need to be activated when partly replacing cement. Moreover, their high specific surface area and irregular shape have a detrimental effect on the workability of concrete; however, mechanical properties and durability exhibit different trends with increasing replacement of IOT in concrete. And we find that on the status of an appropriate replacement IOT can lead to a satisfactory workability, mechanical properties and durability of concrete. Based on previous research, we establish the fundamental correlation between mechanical properties. These conclusions can guide the application of IOT in concrete sustainable technology.